Global justice and the politics of recognition - Burns, Tony.; Thompson, Simon; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Global justice is of every increasing importance in the contemporary political world. This volume brings a hitherto overlooked perspective - the politics of recognition - to bear on this idea. It considers how discussion of each of these illuminates the problems posed by the other, thus addressing an issue of vital concern for the years to come.
Keywords: Science; Science, general